If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11m + 3n + -3m + 10n = 0 Reorder the terms: 11m + -3m + 3n + 10n = 0 Combine like terms: 11m + -3m = 8m 8m + 3n + 10n = 0 Combine like terms: 3n + 10n = 13n 8m + 13n = 0 Solving 8m + 13n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-13n' to each side of the equation. 8m + 13n + -13n = 0 + -13n Combine like terms: 13n + -13n = 0 8m + 0 = 0 + -13n 8m = 0 + -13n Remove the zero: 8m = -13n Divide each side by '8'. m = -1.625n Simplifying m = -1.625n
| 32=3y+2 | | 3x-1=170 | | 22x=4 | | x^2-4x+y=0 | | 20-k=8 | | 3m+1=21 | | 138-3x=24x+18 | | 15=24-3x | | x^3-10x^2+21x-30=0 | | 3y-10x-22=15x-4y+31 | | 3x+114=9x-12 | | 133-2x=34x+17 | | (3z-4)(6+z)=0 | | 6x+8=-122-9x | | 183-2x=43x+23 | | 9-10x=209-45x | | 2x+3(x-5)=5(2x-3) | | 2mn+9mp= | | 4(x+3)-7x=6 | | 10-3x+8=30+2x+48 | | 17x+8=42 | | 9x-6-5x=8+x-14 | | 56-6x=3x+21 | | 5-7x=3x+21 | | -70-9x=43-21x | | (5y-2)=52 | | 14-8x+6-5x=10+2x-5 | | 6x+18=116-6x | | (x+2)(2-x)=6x-x | | 2x+36=21x-36 | | 17-6x=4x-8 | | 9-5k+2k=k-23 |